Uniformity and Diversity in Language Policy Global Perspectives - Hajek, John; Norrby, Catrin (Multilingual Matters, 2011)
This book brings together current research by leading international scholars on the often contentious nature of language policies and their practical outcomes in North America, Australia and Europe. It presents a range of perspectives from which to engage with a variety of pressing issues raised by multilingualism, multiculturalism, immigration, exclusion, and identity. A recurrent theme is that of tension and conflict: between uniformity and diversity, between official policies and real day-to-day life experiences, but also between policies in schools and the corporate world and their implementation. Several chapters present research about language policy issues that has previously not been fully or easily available to an English-language audience. Many of the chapters also provide up-to-date analyses of language policy issues in particular regions or countries, focusing on recent developments